সবাই রাজা অবসর আবাস, an Integrated Retirement Community Raypura, Narsingdi - Ahmed, Ananna (BRAC University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2022.